A one-step immunoassay based on switching peptides for diagnosis of porcine epidemic diarrhea virus (PEDV) using screened Fv-antibodies - Kim, Tae-Hun; Park, Jae-Yeon; Jung, Jaeyong; Sung, Jeong Soo; Kwon, Soonil; Bae, Hyung Eun; Shin, Hyun-Jin; Kang, Min-Jung; Jose, Joachim; Pyun, Jae-Chul (Royal Society of Chemistry, 2024)
In this study, a one-step immunoassay for porcine epidemic diarrhea virus (PEDV) based on Fv-antibodies and switching peptides was developed, and the assay results of PEDV were obtained by just mixing samples without any further reaction or washing steps. The Fv-antibodies with binding affinity to the spike protein of PEDV were screened from the Fv-antibody library using the receptor-binding domain (RBD) of the spike protein as a screening probe. Screened Fv-antibodies with binding affinities to the RBD antigen were expressed, and the binding constants (KD) were calculated to be 83-142 nM. The one-step immunoassay for the detection of PEDV was configured as a displacement immunoassay using a fluorescence-labeled switching peptide. The one-step immunoassay based on switching peptides was performed using PEDV, and the limit of detection (LOD) values for PEDV detection were estimated to be Ct = 39.7-36.4. Compared with the LOD value for a conventional lateral flow immunoassay (Ct = 33.0), the one-step immunoassay showed a remarkably improved LOD for the detection of PEDV. Finally, the interaction between the screened Fv-antibodies and the PEDV RBD was investigated using docking simulations and compared with the amino acid sequences of the receptors on host cells, such as aminopeptidase N (APN) and angiotensin-converting enzyme-2 (ACE-2). In this study, a one-step immunoassay for porcine epidemic diarrhea virus (PEDV) based on Fv-antibodies and switching peptides was developed, and the assay results of PEDV were obtained by just mixing samples without any further reaction or washing steps.